Structural Insights into the Forward and Reverse Enzymatic Reactions in Human Adenine Phosphoribosyltransferase. Issue 6 (21st June 2018) - Huyet, Jessica; Ozeir, Mohammad; Burgevin, Marie-Claude; Pinson, Benoît; Chesney, Françoise; Remy, Jean-Marc; Siddiqi, Abdul Rauf; Lupoli, Roland; Pinon, Gregory; Saint-Marc, Christelle; Gibert, Jean-Francois; Morales, Renaud; et al.
Summary: Phosphoribosyltransferases catalyze the displacement of a PRPP α-1′-pyrophosphate to a nitrogen-containing nucleobase. How they control the balance of substrates/products binding and activities is poorly understood. Here, we investigated the human adenine phosphoribosyltransferase (hAPRT) that produces AMP in the purine salvage pathway. We show that a single oxygen atom from the Tyr105 side chain is responsible for selecting the active conformation of the 12 amino acid long catalytic loop. Using in vitro, cellular, and in crystallo approaches, we demonstrated that Tyr105 is key for the fine-tuning of the kinetic activity efficiencies of the forward and reverse reactions. Together, our results reveal an evolutionary pressure on the strictly conserved Tyr105 and on the dynamic motion of the flexible loop in phosphoribosyltransferases that is essential for purine biosynthesis in cells. These data also provide the framework for designing novel adenine derivatives that could modulate, through hAPRT, diseases-involved cellular pathways. Graphical Abstract: Highlights: Human APRT catalyzes the transformation of adenine into AMP and vice versa Complexes with substrates in both directions of the reaction highlight key residues The catalytic flexible loop dynamic is revealed by an in crystallo activity Tyr105 is essential for cell growth by facilitating the forward reaction Abstract : APRT is a key enzyme in the purine salvage pathway in prokaryotes and eukaryotes. Huyet et al., by using in vitro, cellular, and in crystallo enzymatic analyses, reveal that a hydroxyl group in a conserved tyrosine controls the protein dynamics and the catalytic efficiencies of the forward and reverse reactions.